2015
DOI: 10.1007/s00424-015-1753-x
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular spermine blocks TRPC4 channel via electrostatic interaction with C-terminal negative amino acids

Abstract: Transient receptor potential canonical (TRPC) 4 channels are calcium-permeable, nonselective cation channels and are widely expressed in mammalian tissue, especially in the GI tract and brain. TRPC4 channels are known to be involved in neurogenic contraction of ileal smooth muscle cells via generating cationic current after muscarinic stimulation (muscarinic cationic current (mIcat)). Polyamines exist in numerous tissues and are believed to be involved in cell proliferation, differentiation, scar formation, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Such changes could occur as a result of changes in the fluidity of the surrounding bilayer, through interactions with other proteins and auxiliary subunits, or even as a result of soluble molecules in the cytosol. To give one example, endogenous polyamines, such as spermine and spermidine are known to induce rectification in cationic channels that disappears after patch excision ( Lopatin et al, 1994 ; Kim et al, 2016 ). TRPC6 channels interact with a large number of different proteins ( Bouron et al, 2016 ) and in most cases the functional significance of the interactions are not known but it is not unreasonable to predict that some of these could affect permeation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes could occur as a result of changes in the fluidity of the surrounding bilayer, through interactions with other proteins and auxiliary subunits, or even as a result of soluble molecules in the cytosol. To give one example, endogenous polyamines, such as spermine and spermidine are known to induce rectification in cationic channels that disappears after patch excision ( Lopatin et al, 1994 ; Kim et al, 2016 ). TRPC6 channels interact with a large number of different proteins ( Bouron et al, 2016 ) and in most cases the functional significance of the interactions are not known but it is not unreasonable to predict that some of these could affect permeation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that intracellular spermine strongly blocks TRPC4 channels and inhibits outward cationic current [20]. We also revealed that molecular nature of such inhibition was electrostatic interaction between positive charge of amines (−NH 3 + ) and cytoplasmic negative charge of carboxylic acids of glutamates (E728, E729, −COO − ).…”
Section: Introductionmentioning
confidence: 98%
“…The effect of intracellular polyamine to TRPC4 channel was verified later. With mutant TRPC4 channels, Kim et al showed that glutamate residues at 728th and 729th position are possible binding sites for intracellular spermine [72]. Intracellular spermine reduced outward current dramatically, leaving inward current less changed.…”
Section: Rectificationmentioning
confidence: 99%
“…These residues may attract cytosolic spermine and increase the local concentration of spermine near the channel periphery. Overall effect of E648 and E649 would be reducing access resistance for the following reaction: In a sense, it seems quite surprising that intracellular spermine cannot affect heteromeric channels, i.e., TRPC1/4 and TRPC1/5 channels [72]. Since the I-V curve of heteromeric channels is outwardly-rectifying, intracellular spermine may strongly reduce the outward current if they can exert similar cytoplasmic blocking effect to the heteromeric channel.…”
Section: Rectificationmentioning
confidence: 99%
See 1 more Smart Citation